Pengaruh Pemasaran Berbasis Online Terhadap Peningkatan Penjualan Produk Makanan Skala Rumah Dengan Kepuasan Sebagai Variabel Intervening Di Kecamatan May Bungur - Suwarto; Nina Lelawati; Anggita Dewi Ayu Lestari (Universitas Muhammadiyah Metro, 2025)
The aim of this research is to find out whether online-based marketing has a direct effect onincreasing sales. To find out whether online-based marketing has a direct effect onsatisfaction. To find out whether increasing sales has a direct effect on satisfaction. To findout whether online-based marketing has an indirect effect on increasing sales. Thepopulation in this research is 76 food traders in Way Bungur District. The sample in thisresearch was food traders of Way Bungur District, totaling 32 people. In this research, a pathanalysis model is used because between the independent variable and the dependent variablethere is mediation that influences it. This research consists of three variables. Namely online-based marketing as the independent variable, increasing sales as the dependent variable andsatisfaction as the intervening variable. Based on the results of the research and discussion,several conclusions can be drawn that partially online-based marketing (ξ1) has a positiveand significant influence on increasing sales (η2). There is no direct influence betweenonline-based marketing on satisfaction. There is no direct influence between increasing saleson satisfaction. There is an indirect influence between online-based marketing on increasingsales through the satisfaction variable